2021
DOI: 10.1016/j.asmr.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play After Arthroscopic Stabilization for Posterior Shoulder Instability—A Systematic Review

Abstract: Purpose To ascertain the rate and timing of return to play (RTP) and the availability of specific criteria for safe RTP after arthroscopic posterior shoulder stabilization. Methods Medline, EMBASE, and the Cochrane Library were searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to find studies on arthroscopic posterior shoulder stabilization. Studies were included if they reported RTP data or rehabilitation protocols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…65 Athletes typically target return to sports at around 6 to 8 months after surgery. 65,67,68,70,72 Success in return to play after surgical treatment for anterior and posterior shoulder instability is also variable depending on the sport, position, and nature and severity of injury. In 66 collision athletes, the return to play rate after arthroscopic Bankart repair was 90.9% at a mean of 6 months.…”
Section: Return To Playmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Athletes typically target return to sports at around 6 to 8 months after surgery. 65,67,68,70,72 Success in return to play after surgical treatment for anterior and posterior shoulder instability is also variable depending on the sport, position, and nature and severity of injury. In 66 collision athletes, the return to play rate after arthroscopic Bankart repair was 90.9% at a mean of 6 months.…”
Section: Return To Playmentioning
confidence: 99%
“…73 In a recent systematic review of posterior shoulder stabilization procedures, 25 studies found an overall 62.7% to 100% RTP, with higher return to preinjury level for collision athletes compared with overhead athletes. 72…”
Section: Return To Playmentioning
confidence: 99%
“…5 Most return at 5.8 months (range, 3.2-8 months). 5 In a recent systematic review of the rate, timing, and criteria for return to play after posterior shoulder instability, Fried et al 6 reported that both collision and overhead athletes return to play at similar rates (62.7%-100%) but overhead athletes are more likely to return at a lower level of play. Reinjury rates between 3.4% and 7% were reported.…”
Section: Outcomes Of Shoulder Stabilization Proceduresmentioning
confidence: 99%
“…The findings were similar: Time, imaging, clinical examination, strength, pain, and range of motion were listed as criteria, but none of the studies described objective means of assessment or predetermined thresholds to be met prior to release to unrestricted activity. After procedures addressing posterior instability, Fried et al 6 found no consensus for guidelines to determine when it is safe to return an athlete to play. Again, however, strength, range of motion, time (4-6 months with 6 months most commonly used), absence of pain, completion of a sport-specific rehabilitation protocol, and proprioception were reported.…”
Section: Outcomes Of Shoulder Stabilization Proceduresmentioning
confidence: 99%
“…The timing of return to sports ranges from 4.3 to 8.6 months postoperatively, and collision athletes report a greater rate of return to the preinjury competition level than overhead athletes. 21 Moreover, Katthagen et al 22 found that patients with traumatic posterior instability returned to sports at a higher rate than those with an atraumatic origin (90% vs 72%).…”
Section: Single-portal Shoulder Stabilization E3mentioning
confidence: 99%